Moderasi Beragama di Ruang Digital: Studi Kontribusi Habib Husein Ja’far dalam Menebar Paham Moderat di Kanal Youtube - Ali Mursyid Azisi,; Nur Syam, (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2023)
This article examined Habib Husein Ja’far Al Hadar’s da’wa in the Youtube popular mass media under moderation and religious tolerance. Since the covid-19 pandemic, Habib Husein has continuously upgraded its da'wa spirit spreading peace through Youtube. Through Youtube channels “Jeda Nulis”, “Noice”, and “Cahaya Untuk Indonesia”, Habib Husein was able to engage millennials participating in Islamic discussion by inserting comedy. “Noice” is a da'wa platform accommodating millennials’ rarely-asked questions in da'wa assemblies. The goal is to discover the truth of what Islam advocates, both in video or audio-visual on Youtube. Besides, moderate material on Youtube has attracted millennials' curiosity about religious moderation and tolerance since the covid-19 pandemic. This public figure often filled out the religious discussion with other interfaith leaders (Buddhist and Christian). This article used a qualitative approach to managing, analyzing, and collecting data by investigating relevant and accountable literature in analyzing this research, using Alvin L. Betran's role theory, where the role can come from someone with a certain status or position in the community environment. This writing article's purpose is to find out how was Habib Husein Ja’far da’wa influenced religious moderation and tolerance on Youtube, which intensified during the Covid-19 pandemic. Therefore, the benefits of this research will be as material for knowledge about the urgency of expanding da’wa during the Covid-19 pandemic on social media. And above all, the writer hopes this study will be helpful for academics, future researchers and the general public Indonesia.